Feasibility study of upscaling oxidation of diluted palm oil mill effluent - Ooi, Kai Chuen (2024)
The yearly palm oil production in Malaysia has been rising, contributing to environmental damage from improper disposal of palm oil mill effluents (POME) brought on by inadequate treatment. As a result, the Department of Environment Malaysia and the Malaysian Palm Oil Board wish to strengthen the biochemical oxygen demand (BOD) discharged limit from 100 to 20 ppm. This study proposed UV/H2O2 advanced oxidation technology as a tertiary treatment for treated POME to reduce its BOD to 20 ppm. The optimum concentration of H2O2 and optimum number of UV lights for UV/H2O2 treatment on the POME degradation was determined on a laboratory scale. At the laboratory scale, the UV/H2O2 system utilising 400 ppm of H2O2 and two UV lights has exhibited exceptional performance, achieving 72.3% colour removal efficiency after 6 hours of treatment. Meanwhile, the best UV/H2O2 system performance was yielded in the upscaling experiment under optimal H2O2 concentration with pulse dosing and an optimum number of UV lights to assess its feasibility for industrial application. The upscaling UV/H2O2 treatment with optimum parameters could reduce POME's BOD from 100 ppm to 15 ppm, resulting in 88.4% colour removal efficiency. The UV/H2O2 treatment, during the first three hours in dark conditions, was carried out to determine its feasibility in reducing the BOD of POME to below 20 ppm while saving the cost of treatment. Based on the cost analysis, the UV/H2O2 system working as a post-treatment for POME degradation was economically viable. Subsequently, the phytotoxicity was shown to have decreased in the trials using mung bean seeds. By implementing effective and sustainable POME post-treatment technology, these findings helped to improve the sustainability standards and the financial sustainability of palm oil